2024
DOI: 10.3390/electronics13030512
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Pediatrics: Synthetic Knowledge Synthesis

Jernej Završnik,
Peter Kokol,
Bojan Žlahtič
et al.

Abstract: The first publication on the use of artificial intelligence (AI) in pediatrics dates back to 1984. Since then, research on AI in pediatrics has become much more popular, and the number of publications has largely increased. Consequently, a need for a holistic research landscape enabling researchers and other interested parties to gain insights into the use of AI in pediatrics has arisen. To fill this gap, a novel methodology, synthetic knowledge synthesis (SKS), was applied. Using SKS, we identified the most p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Another important indicator of the research state of a scientific field/sub-field is research funding [17]. Our analysis showed that 41.1% of papers are funded, which is notably more than in many other disciplines [18], however, less than in a comparable subfield, namely the use of AI in pediatrics, where 47.4% of papers were funded [2]. The most prolific funding sponsor is the National Natural Science Foundation of China (n=987), the National Science Foundation, USA (n=284), the National Key Research and Development Program of China (n=226), the Horizon 2020 Framework Programme (n=154), and the European Regional Development Fund (n=105).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Another important indicator of the research state of a scientific field/sub-field is research funding [17]. Our analysis showed that 41.1% of papers are funded, which is notably more than in many other disciplines [18], however, less than in a comparable subfield, namely the use of AI in pediatrics, where 47.4% of papers were funded [2]. The most prolific funding sponsor is the National Natural Science Foundation of China (n=987), the National Science Foundation, USA (n=284), the National Key Research and Development Program of China (n=226), the Horizon 2020 Framework Programme (n=154), and the European Regional Development Fund (n=105).…”
Section: Resultsmentioning
confidence: 84%
“…In the last couple of years, artificial intelligence (AI) has witnessed exponential growth in development, the rise of AI use, and increased public interest on different levels, from individual to organizational [1][2][3]. Modern AI utilizes machine learning and other advanced techniques to generate new knowledge, content, hypotheses, and even innovative ideas by identifying patterns and information usually found in big data-size databases.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometrics is a subfield of informatics that involves the use of mathematical and statistical methods for quantitative and qualitative analysis of published scholarly literature ( 17 19 ). Integrating temporal and spatial dimensions into bibliometric analysis can provide new insights into knowledge development and academic records ( 20 ). This approach focuses on countries, institutions, journals, authors, and keywords associated with a specific field of study, measuring the profile of the field, partnerships, and overall scholarly output.…”
Section: Introductionmentioning
confidence: 99%
“…Another important indicator of the research state of a scientific field/sub-field is research funding [22]. Our analysis showed that 41.1% of papers are funded, notably more than in many other disciplines [18]; however, less than in a comparable sub-fieldnamely, the use of AI in pediatrics, where 47.4% of papers are funded [2]. The most prolific funding sponsor is the National Natural Science Foundation of China (n = 987), the…”
Section: Most Prolific Funding Bodiesmentioning
confidence: 93%
“…In the last couple of years, artificial intelligence (AI) has witnessed exponential growth in development, the rise of AI use, and increased public interest at different levels, from individual to organizational [1][2][3]. Modern AI utilizes machine learning and other advanced techniques to generate new knowledge, content, hypotheses, and even innovative ideas by identifying patterns and information usually found in extensive data-sized databases.…”
Section: Introductionmentioning
confidence: 99%